BioHEAT: A policy decision support tool in Ireland's bioenergy and heat sectors. (1st March 2018) - Durusut, Emrah; Tahir, Foaad; Foster, Sam; Dineen, Denis; Clancy, Matthew
Highlights: Methodology for an integrated bioenergy and heat policy decision support tool. Techno-economic model with a novel representation of consumer decision making. Flexibility to model policy impacts on all 3 energy end use sectors. Method examines supply chain competition from a policy perspective. Results for three scenarios examined to demonstrate the model functionality. Abstract: Bioenergy is likely to play a key role in decarbonising the energy system. The versatility of bioenergy as a transport, heat or electricity fuel is one of its key strengths but can add to the complexity of policy design. Polices aimed at stimulating bioenergy use in one end use sector should consider the impacts of use and uptake in the others. This paper details a methodology for an integrated bioenergy and heat policy decision support tool that is being used to inform policy in Ireland. The previous literature has focused on individual supply chain optimisation, plant sizing and plant locations from an operator's perspective. The BioHEAT model is a techno-economic model that accounts for the co-dependencies between the end use sectors. It extends the approach to supply chain specification in the literature to incorporate a novel representation of consumer decision making in the heat sector and the flexibility to model various policy types in heat, electricity and transport sectors from a policy making perspective. Three scenarios are examined to demonstrate the functionality of the model, including the interaction between separate policies targeting the Heat and Power sectors. The results demonstrate how the model can be used to examine policy impacts against a range of metrics including the contribution to renewable energy and carbon reduction targets; cost to the exchequer and the marginal cost of carbon abated. The model has helped to inform the development of a renewable heat policy instrument in Ireland.